How do reused glide path files affect the cyclic fatigue resistance? = ¿Cómo afecta la reutilización de limas tipo glide path su resistencia a la fatiga cíclica? - Arıcan, Burçin
The aim of this study was to compare the cyclic fatigue resistance (CFR) of PathFile (Dentsply Sirona, Ballaigues, Switzerland) and ScoutRace (FKG Dentaire, La Chaux-de-Fonds, Switzerland) glide path files which were either new or previously used. Forty PathFile (PF) 19/.02 and 40 ScoutRace (SR) 20/.02 instruments were used for this study. Half of the files in each group were used (PF-U and SR-U) in the 3D demo tooth models (FKG Dentaire, La Chaux-de-Fonds, Switzerland) for creating glide paths, while the other half was new (PF-N and SR-N) and directly subjected to the cyclic fatigue test. The new and used files (n=80) were rotated in the cyclic fatigue test device with an artificial stainless-steel canal (60° curvature, 5 mm radius 1.5 mm width and 3.0 mm depth) under the continuous irrigation with distilled water at 37°C until fracture occurred. Time to fracture was recorded and the Weibull reliability analysis was performed. Data were statistically analysed. Conformity to normal distribution was examined using the Shapiro-Wilk test. A paired two-sample t-test was used to compare the TTF values according to the time within the groups. The new instruments (PF-N and SR-N) showed better CFR than the used groups (PF-U and SR-U) (P<0.05). The TTF values of PF were statistically higher than SR in both new and used groups (P<0.05). The predicted time for %99 survival for the files was PF-N> SR-N>PF-U >SR-U. Reuse of both glide path instruments reduced the time to fracture and the cyclic fatigue resistance of the files.